Izrazi za popis upogibnega nihanja palice nespremenljivega prereza - Štubňa, Igor (Strojniški vestnik, 2005)
A short review of the known equations of flexural vibration used for determining the Young's modulus and sound velocity is presented, as well as a new equation that accounts for the rotary inertia and the influence of the shear forces with the term , where iz is the radius of gyration of the cross-section, m is Poisson's ratio, and k is the shape coefficient introducedby Timoshenko. The dispersion curves show a very good fit between the commonly accepted Timoshenko's equation and the new equation derived by Stubňa and Majerník.
Keywords: nihanje upogibno; enačbe diferencialne; izraz Timošenkov; momenti upogibni; upogibno nihanje; modeli